Foreign-language experience in infancy: Effects of short-term exposure and social interaction on phonetic learning - Kuhl, Patricia K. (National Academy of Sciences, 2003)
Infants acquire language with remarkable speed, although little is known about the mechanisms that underlie the acquisition process. Studies of the phonetic units of language have shown that early in life, infants are capable of discerning differences among the phonetic units of all languages, including native- and foreign-language sounds. Between 6 and 12 mo of age, the ability to discriminate foreign-language phonetic units sharply declines. In two studies, we investigate the necessary and sufficient conditions for reversing this decline in foreign-language phonetic perception. In Experiment 1, 9-mo-old American infants were exposed to native Mandarin Chinese speakers in 12 laboratory sessions. A control group also participated in 12 language sessions but heard only English. Subsequent tests of Mandarin speech perception demonstrated that exposure to Mandarin reversed the decline seen in the English control group. In Experiment 2, infants were exposed to the same foreign-language speakers and materials via audiovisual or audio-only recordings. The results demonstrated that exposure to recorded Mandarin, without interpersonal interaction, had no effect. Between 9 and 10 mo of age, infants show phonetic learning from live, but not prerecorded, exposure to a foreign language, suggesting a learning process that does not require long-term listening and is enhanced by social interaction.